The Return to Firm Investment in Human Capital - Almeida, Rita; Carneiro, Pedro (World Bank, Washington, DC, 2012)
In this paper the authors estimate the rate of return to firm investments in human capital in the form of formal job training. They use a panel of large firms with unusually detailed information on the duration of training, the direct costs of training, and several firm characteristics such as their output, workforce characteristics, and capital stock. Their estimates of the return to training vary substantially across firms. On average it is -7 percent for firms not providing training and 24 percent for those providing training. Formal job training is a good investment for many firms and the economy, possibly yielding higher returns than either investments in physical capital or investments in schooling. In spite of this, observed amounts of formal training are small.